Intertextualidade na imprensa escrita: uma leitura de crônicas esportivas do jornal Folha de S. Paulo - Prado, Losana Hada de Oliveira (2009)
The objective of this research is to study the chronicles written by José Geraldo Couto, Eduardo Gonçalves de Andrade (Tostão), José Roberto Torero, José Carlos Amaral Kfouri (Juca kfouri) and Xico Sá in the sporting section of the newspaper Folha de S. Paulo, examining the traces of the intertextuality. The research aims at contributing to the studies of texts, verifying how intertextual processes can determine the production of meaning. In order to achieve that, we have grounded the dissertation in the light of bakhtinian studies, Text Linguistic and Discourse Analysis. Considering that a text is composed by others texts and at the same time is part in the other texts, the identification of the intertexture is important to produce the meaning in the chronicle reading. The analysis was carried out so as to contemplate theoretical analytical procedures. In this sense, the cognitive principles attached to others stand out. The results obtained have evidenced that the reader must activate his previous knowledge and identify the intertextuallity to build the main idea in the opinion sections reading. All the procedure of this research proves that the development of the studies about intertextuallity can no longer be conceived of pure texts or of unbiased authorship